Performance of construction company in Malaysia during recession market based on internal factors (financial) / Siti Nor Hayati Abdullah - Abdullah, Siti Nor Hayati (2012)
The Construction sector consists of establishments engaged in constructing, renovating, and demolishing buildings and other engineering structures. The sector includes contractors in commercial, residential, highway, and heavy industrial (e.g., tunnels, airports, and dams) and municipal utility construction (e.g., wastewater treatment plants). Specialized trades within the sector include work that is commonly subcontracted such as plumbing, heating, masonry, and painting. The construction industry plays a major roles as a key indicator and determinant of domestic performance in the economy.it is argued that the most significant factors that affect all construction demand is general economic situation and expectation that how it will change. In Malaysia, the construction sectors is the third-biggest productivity sectors after manufacturing and agriculture. The construction industry has a strong influence on growth because of the extensive backward and forward linkage with the rest of the economy. However, despite being known as one of the most contributive sectors in the developing economy of country. There is still lack of appropriate attention given to the development of the industry and its contractors